Comparative analysis of international legal regulation and practice of foreign countries in providing access to information: integration of regulatory and practical approaches - Digay, Damir; Nurmukhankyzy, Daniya; Taubayev , Baurzhan (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article presents a comparative analysis of the international legal regulations and practices of foreign countries regarding access to information. Its aim is to explore how normative and practical approaches combine in guaranteeing access rights both internationally and across different nations. Key areas of analysis include regulations, their application in practice, and mechanisms for monitoring the implementation of such norms. This work is of great scientific and practical significance, helping us to gain a greater understanding of differences and similarities in approaches taken towards regulating access to information. This can serve as the basis for developing recommendations to strengthen legislation in this area. Comparative analysis, legal dogmatics, and analysis of law enforcement practice were utilized during this research project. The main findings demonstrate that, despite global standards, implementation of accessing information varies considerably according to national context. As a result, our findings highlight the necessity of considering international experience when developing national regulatory frameworks and practices. This study offers a great value by offering a systematic analysis of international and national regulatory and practical mechanisms in relation to access to information. Furthermore, its practical significance lies in being used by regulators and practitioners across different nations in improving access to information rules and practices. .